Social inequalities in osteoporosis and fracture among community dwelling older men and women: findings from the Hertfordshire Cohort Study - Syddall, Holly E (2012)
INTRODUCTION: Osteoporosis and osteoporotic fracture are major public health issues for society; the burden for the affected individual is also high. It is unclear whether osteoporosis and osteoporotic fracture are socially patterned. OBJECTIVE: To analyse social inequalities in osteoporosis and osteoporotic fracture among the 3,225 community dwelling men and women, aged 59-73 years, who participated in the Hertfordshire Cohort Study (HCS), UK. METHODS: A panel of markers of bone health (fracture since 45 years of age; DXA bone mineral density and loss rate at the total femur; pQCT strength strain indices for the radius and tibia; and incident fracture) were analysed in relation to the social circumstances of the HCS participants (characterised at the individual level by: age left full time education; current social class; housing tenure and car availability). RESULTS: We found little strong or consistent evidence among men, or women, for social inequalities in prevalent or incident fracture, DXA bone mineral density, bone loss rates, or pQCT bone strength, with or without adjustment for age, anthropometry, lifestyle and clinical characteristics. Reduced car availability at baseline was associated with lower pQCT radius and tibia strength strain indices at follow-up among men only (p=0.02 radius and p<0.01 tibia unadjusted; p=0.05 radius and p=0.01 tibia, adjusted for age, anthropometry, lifestyle and clinical characteristics). CONCLUSIONS: Our results suggest that fracture and osteoporosis do not have a strong direct social gradient and that public health strategies for prevention and treatment of osteoporosis should continue to focus on the whole population.